A Study on Antioxidant Activity from Canavalia rosea Leaves Extract: Studi Aktivitas Antioksidan dari Ekstrak Daun Canvalia rosea - fauzianoprima okta; Relin Yesika; Septi Wulandari; Etriyanto Arman; Kharunia Tri Utami; Farah Az-Zahra (JURNAL FARMASI DAN MAKANAN, 2025)
Canavila rosea is a herbaceous plant in the Leguminosae family, commonly known as beach beans. C. rosea is naturally found along coastal areas, including the coast of Bengkulu. Beach beans leaves contain phenolic compounds, flavonoids, tannins, alkaloids, and saponins that have the potential to be developed as antioxidants. Antioxidant activity is the basis for the development of other treatments such as antidiabetic, antibacterial, anti-tyrosinase, and anticancer agents. Based on the potential, this study aims to test the antioxidant activity of beach beans leaf extract. Antioxidant activity is also related to flavonoid content, especially flavonoids bound to sugar group. The extraction method uses the Soxhlet method. Qualitative flavonoid content testing is carried out using flavonoid phytochemical screening reagents. Quantitative flavonoid content testing is carried out using the Chlorimetric method. Antioxidant testing uses the DPPH inhibition method. The yield percentage of 96% ethanol extract was 26%. The results showed that C. rosea extract contained flavonoid compounds. Antioxidant activity showed an IC50 value of 77,09±3,18 µg/mL for the ethanol extract. The total flavonoid content of the ethanol extract was 4.791 ± 0.93 %. The ethanol extract has strong antioxidant activity with an IC50 value in the range of 50-100 ppm.